Suboptimal child spacing practice and its associated factors among women of child bearing age in Serbo town, JIMMA zone, Southwest Ethiopia - Girma Bacha Ayane; Kalkidan Wondwossen Desta; Birhanu Wondimeneh Demissie; Netsanet Abera Assefa; Emebet Berhane Woldemariam (BMC, 2019)
Abstract Introduction Birth spacing is the time gaps between two consecutive life births. Optimal spacing until the next pregnancy is the resting period that allows the mother time to recover from pregnancy, and labor. Birth interval of 3 to 5 years increases maternal health and child survival and family planning programs have advocated this birth interval. Objectives To assess prevalence of Suboptimal Child spacing practice and its associated factors among Women of Child bearing age in Serbo town, Jimma Zone Southwest Ethiopia. Methods Community based cross sectional study was conducted on a total of 314 women of child bearing age from March to April 2017 who were selected by simple random sampling. A semi structured questionnaire which was pretested was used to collect the data. Data was checked for completeness and analyzed using SPSS V.20. Bi-variable logistic regression and multi- variable regression were done for predictor variables associated at p-value < 0.05 with the outcome variable. Result The prevalence of short birth interval in this study was 59.9%. Independent predictors like age at first marriage (AOR: 2.10, 95% CI = 1.19, 3.69), sex of index child (AOR: 1.964, 95% CI = 1.05 3.96), educational status (AOR: 3.05,95% CI = 1.68, 3.83), duration of breastfeeding (AOR: 3.09, 95% CI = 1.38, 6.96) and use of modern contraceptives (AOR: 1.94, 95% CI = 1.09, 3.45) were found to be statistically associated with short birth interval. Conclusion and recommendation Majority of the study respondents were practicing short birth interval. Education level, age at first marriage, having female child, short duration of breastfeeding and not using of modern contraceptives were factors associated with the outcome variable. Therefore awareness about modern contraceptive utilization, importance of breastfeeding as birth spacing mechanism and impact of early marriage are recommended.